Community Motivation for Selecting Zakat, Infaq, and Sadaqah Payment Methods Using Fintech Platform - Tartila, Muzayyana (ZISWAF, 2022)
From time to time, the amount of zakat, infaq, and sadaqah collected increases. Due to the fact that the collection of zakat, infaq, and sadaqah has not yet reached its full potential, it is crucial to study Muzakki's behavior on the fintech platform. This study expands on prior research by introducing new variables based on knowledge of internal and external factors. This study employed a qualitative approach. Nine samples were obtained through Muzakki from individuals who had paid zakat, infaq, and sadaqah through the fintech platform. This study's data analysis involved data reduction, data presentation, and conclusion drawing. According to research, Muzakkis have diverse motivations for selecting fintech platforms as payment methods for zakat, infaq, and sadaqah. They cited internal considerations as the primary reason for selecting the QRIS and CoopLink fintech platforms as zakat, infaq, and sadaqah payment platforms. Then, external factors are influenced by the workgroup that an individual joins and the surrounding environment. Regardless of the diversity of motivational factors in this study, all informants felt the same way when using the fintech platform to pay zakat, infaq, and sadaqah: curiosity and ease. And based on the findings of this study, it is possible to conclude that the selection of the appropriate payment method can influence the collection of zakat, infaq, and sadaqah.